Determination of Cisplatin Effect on Head and Neck Squamous Cell Carcinoma Modulated by Erk1/2 Protein Kinases - Marinela Bostan; Georgiana Gabriela Petrica-Matei; Gabriela Ion; Nicoleta Radu; Mirela Mihaila; Razvan Hainarosie; Lorelei Irina Brasoveanu; Viviana Roman; Carolina Constantin; Monica Teodora Neagu (Current Practice in Medical Science Vol. 8, 2022)
The purpose of this research was to find out how curcumin (CRM) used as an adjuvant supports the apoptotic process induced by a mono chemical agent treatment (cisplatin-CisPT) on two head and neck squamous cell carcinoma cell lines (FaDu and PE/CA-PJ49) and the involvement of extracellular signal-regulated kinases (ERK1/2) and/or p53 activation in this process. Data indicate that CRM potentiates the CisPt action. CRM increased the phosphorylation of the p53 protein in both cell lines. In FaDu cells, CisPt reduced the phosphorylation of the p53 protein, whereas in PE/CA-PJ49 cells, it increased. In the two examined tumour cell lines, constitutive expression of activated ERK1/2 protein-kinase was different. Both cell processes, proliferation, and death triggered by CisPt and/or CRM depended on the activation status of ERK1/2. Our findings imply that ERK1/2 may be necessary for the phosphorylation of p53 during the apoptotic process triggered by CRM therapy. Apoptosis induced by combined treatments (CisPt and CRM) was p53 phosphorylation-ERK1/2 activation-dependent in both tumor cell lines. Finally, depending on the type of therapeutic agent, the characteristics of the cells, and the ERK1/2 activation status, ERK1/2 may influence cell proliferation and/or apoptosis.